2013
DOI: 10.1097/meg.0b013e32835ad180
|View full text |Cite
|
Sign up to set email alerts
|

The effect of hemodialysis on liver stiffness measurement

Abstract: This study is the first to report on the influence of hemodialysis on liver stiffness measurement. In contrast to previous reports, liver stiffness might increase after fluid withdrawal if patients do not show significant fibrosis. We conclude that before dialysis, TE possibly better differentiates between patients with or without significant fibrosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 25 publications
1
12
0
Order By: Relevance
“…The withdrawal of fluid during HD influences liver stiffness measurement results, even in patients without viral hepatitis infection. Kellner et al showed that a significant increase in liver stiffness measurement was found after HD in patients with an initial level lower than 7.1 kPa (28). In our study, for patients with chronic viral hepatitis, F3 stage liver fibrosis was a risk factor for TCP.…”
Section: Discussionsupporting
confidence: 52%
“…The withdrawal of fluid during HD influences liver stiffness measurement results, even in patients without viral hepatitis infection. Kellner et al showed that a significant increase in liver stiffness measurement was found after HD in patients with an initial level lower than 7.1 kPa (28). In our study, for patients with chronic viral hepatitis, F3 stage liver fibrosis was a risk factor for TCP.…”
Section: Discussionsupporting
confidence: 52%
“…Sample size calculation was carried out from the mean LSM difference of 1.5 kPa and σ of 2.6 [14] , with a 2-tailed α of 0.05 and a power (β) of 0.80. Thus, 32 patients were required in each group.…”
Section: Resultsmentioning
confidence: 99%
“…As such, TE may have some limitation in patients with fluid overload. Recently, a study showed an increase in LSM after HD in a group with an initial TE <7.1 kPa (p = 0.05) [14] . Nevertheless, the difference of pre-and post-HD LSMs in ESRD patients could not be demonstrated in our study.…”
Section: Discussionmentioning
confidence: 97%
“…A decision tree for the follow-up process is shown in Figure 1. Treating HCV infection prior to KT helps to prevent post-transplantation complications and reduce mortality [3,[39][40][41][42] . There is general agreement that ESRD patients with decompensated cirrhosis and portal hypertension should be removed from the KT list and referred to the liver transplant team to be considered for combined liver-KT [43] .…”
Section: Diagnosis Of Hcv Infection In Patients With Esrdmentioning
confidence: 99%
“…Studies have demonstrated that APRI and TE are effective for evaluating hepatic fibrosis in HD patients with chronic HCV infection, but both methods have some limitations [37,38] . The predictive values and cut-off values for these methods as optimized for the healthy population may not be valid for ESRD patients [39] . As well, the HD procedure and the presence of uremic toxins may alter blood levels of apolipoprotein A1 and α-2 macroglobulin, which can influence Fibroscan ® results [37] .…”
Section: Diagnosis Of Hcv Infection In Patients With Esrdmentioning
confidence: 99%